ASSOCIATION OF MACRONUTRIENT INTAKE WITH PERCENTAGE OF VISCERAL FAT IN INTERNATIONAL STUDENT AT UNIVERSITAS AIRLANGGA SURABAYA - Salmiah Ibrahim Baswedan; Sri Sumarmi (Media Gizi Indonesia, 2021)
Diets are often associated with nutritional status of a person. Good nutritional status always accompany a good diet, if the intake of food is good, then it will give a good nutritional status as well. If energy intake exceeds output energy along with low physical activity, so it can lead to a build up of fat and increase the risk of overweight and obesity. The purpose of this research was to analyze the relationship between macronutrient intake with visceral fat on foreign students Universitas Airlangga in Surabaya. This study is observational, cross-sectional research design. The research sample was 65 students, where subjects was determined by purposive with inclusion criteria that had stayed at least 6 months in Indonesia, healthy, and not on a diet. The independent variable is the level of macro nutrient adequacy. The dependent variable is the visceral fat. Data were analyzed using chi-square test with a signifi cance level of <0.05 and linear regression. Results showed that there was a signifi cant relationship between energy suffi ciency level (p = 0.000) and fat (p = 0.018) with percentage of visceral fat. Every 1% increase in level of energy suffi ciency, respondent’s percentage of visceral fat will increase by 3.589. Every additional 1% of level of fat suffi ciency, percentage of visceral fat will increase by 1.712. The higher the intake of energy and fat, there will be an increase in visceral fat. The conclusion of this study is energy and fat intake can increase visceral fat. Increasing energy suffi ciency and fat will increase visceral fat as well.